An exploration and expansion of learning and agency in ecosystem restoration practice - Thifhulufhelwi, Reuben (Rhodes University, 2026)
This study explores and expands learning processes in restoration natural resource management (NRM) practices. The study uses the theory of expansive learning, developed in the Finnish Cultural-Historical Activity Theory tradition, to examine how expansive learning develops transformative agency that enables practitioners and key stakeholders to envisage new pathways that enhance collective actions to manage natural resources as a sustainability commons for all. The study was conducted in the Blyde River Catchment landscape in the Mpumalanga and Limpopo provinces of South Africa. The study is located in the field of Environment and Sustainability Education, with emphasis on addressing complex socioecological issues including degradation of biodiversity and water resources, access to ecosystem services for livelihoods, and capacity development of local stakeholders to become custodians and responsible managers of their own natural resources. Within the field of Cultural-Historical Activity Theory, which this study draws on and is guided by from both a theoretical and methodological perspective, the study straddled third generation Cultural-Historical Activity Theory, with movement in the study evident towards the fourth generation of Cultural-Historical Activity Theory. The study took place over an eight-year period (2016 – 2024), and was divided into two phases, roughly demarcated around this shift in the research process as the expansive learning work expanded and became more complex in the field. Part I of the study involves exploring the historical context and current initiatives in restoration NRM practice to surface tensions and contradictions constraining collective action at the catchment scale. These contradictions were addressed by facilitating a longitudinal expansive learning process using a formative interventionist research approach, a process that started in 2016. Formative interventionist research is a form of collaborative inquiry that focuses on building transformative agency with stakeholders across activity systems, to develop new learning actions and tools relevant to their shared object of activity. In the case of this study, the shared object of activity was to address socio-ecological issues in restoration NRM practices. Part II of the study, which emerged from Phase I in 2019/2020, further facilitated the formative intervention engagements with a specific focus on developing practical tools such as implementation strategies, and plans, establishing working groups and networks, training and capacity development initiatives, as well as developing funding proposals as learning tools to enable stakeholders to work collectively in the implementation and governance of restoration NRM practices at landscape level. These are described as double stimulation processes leading to Emancipatory Transformative Agency by Double Stimulation (ETADS) along linked, and parallel pathways involving constellations of activity systems. This study demonstrates how co-engaged expansive learning programmes, implemented as longitudinal formative interventions, can lead to the emergence of transformative agency that not only enables stakeholders to work together to practically advance their shared object of activity but also to re-imagine their ethical–political intentions towards enacting sustainability actions and socio-ecological justice. The study provides analytic tools and concepts for engaging and navigating complex societal issues which emerge in social-ecological activity expansions. In particular, the study focuses on power-dynamics contradictions embedded in structures of power and decision making. This study surfaced power-dynamics contradictions that were constraining practitioners and communities and explored how these were navigated in collective engagement and expansion of the object of restoration NRM practices in the interest of the common good. Overall, the study offers a case of transitioning between third and fourth generation Cultural-Historical Activity Theory research. It surfaces theoretical, conceptual, contextual, mediational and outcome-related insights that emerged through such a process in the Blyde landscape.
a case of natural resource management programmes in the Blyde Catchment, South Africa
Keywords: Uncatalogued